Digital and traditional marketing approaches by BRAC EPL Stock Brokerage Ltd. - Khan, Maisha Rafa (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.